Comparison between Endoscopic Ultrasound-Guided Antegrade and Transluminal Stent Implantation in Distal Malignant Biliary Obstruction after Failed ERCP - Yonghua Shen; Ying Lv; Xiaojiao Zheng; Wei Zhan; Senlin Hou; Lin Zhou; Jun Cao; Bin Zhang; Lei Wang; Hao Zhu; Lichao Zhang (Gastroenterology Research and Practice)
Background. Distal malignant biliary obstruction (DMBO) can result in obstructive jaundice. Endoscopic ultrasound- (EUS-) guided biliary drainage (EUS-BD) has been an alternative for DMBO after failed ERCP. Aim. To compare the efficacy and safety between antegrade and transluminal approaches in patients with unresectable DMBO when ERCP failed. Methods. Patients with DMBO leading to obstructive jaundice after failed ERCP were enrolled in this study. We retrospectively evaluated the safety and efficacy between EUS-guided transluminal stenting (TLS group) and antegrade stenting (AGS group). Results. 82 patients were enrolled, of which 45 patients were in TLS group and 37 in AGS group. There were no statistical differences in the malignancy type, baseline common bile duct diameter, total bilirubin level, reason for EUS-BD, and history of biliary drainage between TLS and AGS groups. The technical success rate was statistically higher in TLS group than in AGS group (97.8 vs. 81.1%, P=0.031). There were no statistical differences in clinical success rate, procedure-related adverse events, stent migration rate, stent dysfunction rate, reintervention rate, and overall patient survival time between TLS and AGS groups. The median time to stent dysfunction or patient death in TLS and AGS groups was 53 and 81 days, respectively (P=0.017). Conclusions. Although AGS had a lower technical success rate than TLS, it was superior to TLS in stent patency in patients with DMBO.